Application of Targeted Proteomics in Food Safety Detection - CHEN Mengqi, PENG Miaoxi, LIU Jingwen, HUANG Chengdong, WU Zuqing, LING Li, YUAN Muyun, CHEN Wenrui, HU Songqing (Shipin Kexue)
Food safety is a major global public health concern. Targeted proteomics based on mass spectrometry (MS) plays an increasingly important role in addressing this issue due to its high sensitivity, specificity, and quantitative accuracy. In this article, two common targeted proteomics approaches including multiple reaction monitoring (MRM) and parallel reaction monitoring (PRM) are briefly introduced. The progress that has been made in the application of targeted proteomics in food safety detection in the last five years is summarized including authentication of animal-derived foods, analysis of food allergens, and detection of foodborne pathogens and their toxins. Meanwhile, an outlook on the future development of this field is given.